2017
DOI: 10.1557/jmr.2017.200
|View full text |Cite
|
Sign up to set email alerts
|

Spiky niobium oxide nanoparticles through hydrothermal synthesis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Increasing the temperature to 190 °C, the approximate major axis length increased to 30 nm, and the nanorods were separated from each other (Figure 1j–l and S4, Supporting Information). There was no change in morphology between 190 and 200 °C samples, and as in previous reports, [ 14,17,18 ] the spiky Nb 2 O 5 nanoparticles composed of a spherical core and numerous nanorods were obtained (Figure 1m–o and S5, Supporting Information). These results suggested that the nanorods grew by migration not only from a spherical core but also among primal particles, rectangular‐shaped nanoarchitectures, and nanorods.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Increasing the temperature to 190 °C, the approximate major axis length increased to 30 nm, and the nanorods were separated from each other (Figure 1j–l and S4, Supporting Information). There was no change in morphology between 190 and 200 °C samples, and as in previous reports, [ 14,17,18 ] the spiky Nb 2 O 5 nanoparticles composed of a spherical core and numerous nanorods were obtained (Figure 1m–o and S5, Supporting Information). These results suggested that the nanorods grew by migration not only from a spherical core but also among primal particles, rectangular‐shaped nanoarchitectures, and nanorods.…”
Section: Resultssupporting
confidence: 88%
“…Oxalic acid, which has two carboxyl groups, must adsorb on Nb 2 O 5 in hydrothermal synthesis and suppress particle growth similar to acetate ions. However, considering the decomposition temperature of oxalic acid to formic acid and carbonate ions around 180–200 °C, [ 18 ] it will disappear from the surface and lose the protecting function. Therefore, as shown in Figure 3 , we have proposed the growing mechanism of a spiky nanostructure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, rough and ''spiky'' spheres could be used as catalysts due to their larger surface. 29 Moreover, ''smooth spheres'' with nanometric dimensions can easily enter cells and be applied in drug delivery and photodynamic therapy. 30 Finally, hydrogels can be utilized for biomedical applications.…”
mentioning
confidence: 99%
“…Surfactants with one coordination site (e.g., oleic acid, oleylamine, carbonic acid, nitric acid, and acetate acid) are commonly used to generate simple 0D to 3D nanostructures such as nanocubes, nanorods, and nanosheets [16,26,27]. In contrast, surfactants with two or more coordination sites (e.g., urea, phosphoric acid, and oxalic acid) are often used to synthesize complex 3D nanostructures [23,24,25,28,29,30,31,32]. Coordination molecules with one coordination site adsorb on particle surfaces to suppress particle aggregation, particle growth, and the growth of specific crystal planes, resulting in simple structures.…”
Section: Introductionmentioning
confidence: 99%